Effect of frequency and temperature on dielectric and impedance characteristics of cerium modified BaMnO3 ceramics. (2022) - Meher, S.; Satpathy, T.; Sa, Chandini; Mishra, S.; Choudhary, RNP; Parida, S.K.
Abstract: In this paper, we have mainly discussed the electric field (frequency) and thermal (temperature) effect on dielectric, and electrical (impedance, electrical, and conduction) properties of a solid-state reaction technique prepared cerium modified barium manganite (BaMn0.85 Ce0.15 O3 ). The dielectric study exhibits high dielectric constant, low tangent loss, dielectric dispersion, and negative temperature coefficient of resistance characteristics which makes the material useful for energy storage devices. Preliminary analysis of the impedance and electric modulus suggests the presence of a non-Debye type of relaxation process and the role of grain and grain boundaries in the resistive and capacitive properties of the material. Both Nyquist and Cole-Cole plots confirm the semiconductor nature of the sample at high temperatures. The fitted Nyquist data with ZSIMPWIN software showed the decrease of bulk resistance from 8.841 × 10 7 Ω (at 25 °C) to 4.085 × 10 3 Ω (at 500 °C) which also confirms semiconducting properties and may be found suitable applications for sensors. The analysis of ac conductivity suggests the presence of the thermally activated relaxation process in the sample.